Penerapan Hak-Hak Narapidana di Lembaga Pemasyarakatan Kelas IA Tanjung Gusta, Sumatera Utara Ditinjau dari Perspektif Hak Asasi Manusia - Donny Michael (Jurnal HAM, 2015)
Correctional Institutions has been working to provide advisory services to the Prisoners, so that the rights of Prisoners are fulfilled. The research aims to find the factors supporting and inhibiting the implementation of the rights of Prisoners at the Correctional Institution, and found the effort to implement the rights of Prisoners in accordance with a human rights perspective. The research method is descriptive with qualitative approach. The results showed a limiting factor, among others, (1) relative to the classical normative happened for a long time about the excess of prisoners, budget constraints, lack of coordination among government agencies, (2) as well as technical and administrative documents that must be held Prisoners for be able to obtain their rights, (3) the dynamics of law in the treatment of Prisoners. Supporting factors come from the Prisoners and prison officers in running coaching programs in prisons and the legal products such Circular Letter of of the Minister of Justice and Human Rights of the Republic of Indonesia specifically related to the implementation of the provisions of justice collaborator. Efforts implementation of the rights of Prisoners in terms of the perspective of human rights has been made by the Government cq. Directorate of Corrections, although admittedly there are limitations that can not be addressed effectively. Normatively it is reflected in Article 14 paragraph (1) of Law No. 12 of 1995 on Corrections. Recommendation: Review the provisions of Article 34A paragraph (1) and Article 43A paragraph (1) of Government Regulation No. 99 Year 2012 on the Second Amendment to Government Regulation No. 32 of 1999 on the Terms and Procedures for Residents Rights Patronage; Requirement justice collaborator regulated in Government Regulation contrary to the spirit of Article 14 of Law No. 12 of 1995 on Corrections. Justice collaborator can not be used as a condition to get Remission and Parole; Reviewing Article 50 paragraph (1) of the Regulation of the Minister of Law and Human Rights No. 21 of 2013 regulating the family collateral requirements for obtaining conditional rights